Effect of Shogaol on the Expression of Intestinal Stem Cell Markers in Experimentally Induced Colitis in BALB/c Mice - Snur M. A. Hassan; Ali Hussein Hassan (Analytical Cellular Pathology)
Aim. This study is aimed at investigating the effect of Shogaol, a phenolic constituent of ginger, on dextran sodium sulfate- (DSS-) induced ulcerative colitis (UC) in mice in comparison with 6-thioguanine (6-TG), an immune-suppressant chemotherapeutic medicine used for treatment of ulcerative colitis. Material & Methods. Thirty-six adult, male and female BALB/c mice were randomly divided into six groups: group 1 (control negative) not exposed to DSS and did not receive any treatment, group 2 (control positive) exposed to DSS but did not receive any treatment, group 3 exposed to DSS and treated by 0.1 mg/kg of 6-thioguanine, and groups 4, 5, and 6 exposed to DSS and treated by 10, 20, and 40 mg/kg b.w. Shogaol, respectively. At day 56, the mice were checked for their disease activity index (DAI) and they were sacrificed. The colons of the mice were examined for length measurement, histological index score, and the expression of CD133 and CD34 stem cell markers. Results. Shogaol showed a better curative effect than did 6-TG in repairing the colonic mucosal damages in DSS-exposed mice as indicated by the levels of CD133 and CD34 expression in the colonic crypts and by the DAI score, colon length measurements, & histological index score which were significantly reduced in mice treated by Shogaol, particularly the 20 and 40 mg/kg BW doses. Conclusion. The results of this study indicated that oral treatment with the ginger-derived substance Shogaol could be better than the conventional immunosuppressive chemotherapeutic remedy 6-TG in treatment of DSS-induced UC.